Does religious fasting affect cognitive performance? - Mohd Yasin, Wardah; Khattak, Muhammad Muzaffar Ali Khan; Mamat, Nik Mazlan; Mohd Abu Bakar, Wan Azdie (2013)
Purpose – The purpose of this article is to assess the effect of religious fasting on the cognitive performance during the month of Ramadan among healthy fasting individuals.